2011
DOI: 10.1162/jocn.2010.21560
|View full text |Cite
|
Sign up to set email alerts
|

Load Modulation of BOLD Response and Connectivity Predicts Working Memory Performance in Younger and Older Adults

Abstract: ■ Individual differences in working memory ( WM) performance have rarely been related to individual differences in the functional responsivity of the WM brain network. By neglecting person-to-person variation, comparisons of network activity between younger and older adults using functional imaging techniques often confound differences in activity with age trends in WM performance. Using functional magnetic resonance imaging, we investigated the relations among WM performance, neural activity in the WM network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
140
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(175 citation statements)
references
References 88 publications
(116 reference statements)
31
140
2
Order By: Relevance
“…In addition, non-phase locked activity reflecting the suppression of irrelevant information was also impaired in this group. Similar to other recent studies (Duverne et al, 2009;Nagel et al, 2009Nagel et al, , 2011Schneider-Garces et al, 2010), the present results underscore the heterogeneity of WM and episodic memory functioning among older adults, and are consistent with the proposition that older adults with more "youth-like" processing patterns tend to show higher levels of performance (e.g., Nagel et al, 2009). The present results are in line with a recently proposed conceptual framework for studying lifespan changes in episodic (Shing et al, 2008Werkle-Bergner et al, 2006) and working memory (Sander et al, 2011a(Sander et al, , 2011b, that dissociates the contributions of low-level feature binding and (strategic) control components to adult age differences in memory performance.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, non-phase locked activity reflecting the suppression of irrelevant information was also impaired in this group. Similar to other recent studies (Duverne et al, 2009;Nagel et al, 2009Nagel et al, , 2011Schneider-Garces et al, 2010), the present results underscore the heterogeneity of WM and episodic memory functioning among older adults, and are consistent with the proposition that older adults with more "youth-like" processing patterns tend to show higher levels of performance (e.g., Nagel et al, 2009). The present results are in line with a recently proposed conceptual framework for studying lifespan changes in episodic (Shing et al, 2008Werkle-Bergner et al, 2006) and working memory (Sander et al, 2011a(Sander et al, , 2011b, that dissociates the contributions of low-level feature binding and (strategic) control components to adult age differences in memory performance.…”
Section: Resultssupporting
confidence: 92%
“…Nevertheless, speculative hints on the possible neuroanatomical difference may be derived from fMRI findings. In line with the present report, recent investigations of age-differences in fMRI activation patterns during WM-tasks demonstrate a dependence of the ability to modulate neuro-vascular responses on the individual performance level (e.g., Nagel et al, 2009Nagel et al, , 2011Schneider-Garces et al, 2010). In addition, Hedden et al (in press) could link a failure to modulate fMRI responses according to attentional demands in a subset of their older participants to elevated white matter hyperintensity (WMH) burden.…”
Section: Performance Related Differences In the Control Of Wm-contentsupporting
confidence: 89%
See 1 more Smart Citation
“…This result matches the previous work on this topic (Cusack, Mitchell, & Duncan, 2010;Galy, Cariou & Mélan, 2011;Nagel et al, 2011;Tregellas, Davalos & Rojas, 2006), which has shown that these results are highly predictable from a neuro-cognitive perspective (see Schneider, 1999 for a review).…”
Section: Discussionsupporting
confidence: 91%
“…Several recent studies have looked at specific functional connections during a task, and how these are affected by age. One study examined changes in brain activity during a working memory task with varying degrees of difficulty 87 and found that young adults had load-dependent increases of activity in PFC. Older adults showed relatively high levels of PFC activity across all load levels (consistent with CRUNCH, see above), and weaker functional connectivity between the premotor cortex and a left dorsolateral PFC region.…”
Section: Brain Network and Functional Connectivitymentioning
confidence: 99%